1998
DOI: 10.1002/(sici)1096-9861(19980119)390:3<342::aid-cne4>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Auditory brainstem projections to the ferret superior colliculus: Anatomical contribution to the neural coding of sound azimuth

Abstract: The mammalian superior colliculus (SC) contains a neural map of auditory space. It is not known whether this topographic representation emerges at the level of the SC or is relayed there from other auditory areas. We have used retrograde labelling techniques in ferrets to examine the sources and pattern of innervation from auditory brainstem nuclei. After multiple injections of wheat germ agglutinin conjugated to horseradish peroxidase (WGA-HRP) into the SC, the heaviest concentrations of labelled cells were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(36 citation statements)
references
References 65 publications
2
34
0
Order By: Relevance
“…Anatomical studies in several species have shown that the nBIC provides a large projection to the dSC (Edwards et al 1979;King et al 1998a) and recordings in both ferrets (Schnupp and King 1997) and cats (Aitkin and Jones 1992) have confirmed that nBIC neurons are acoustically responsive and have spatially tuned receptive fields. The tracing data presented here show that nBIC neurons extend axons that terminate in the dSC, suggesting that this pathway is also likely to provide a major route in by which auditory information reaches the SC in rats.…”
Section: Multisensory Circuits In the Slice: Specificity Of Afferent mentioning
confidence: 98%
See 2 more Smart Citations
“…Anatomical studies in several species have shown that the nBIC provides a large projection to the dSC (Edwards et al 1979;King et al 1998a) and recordings in both ferrets (Schnupp and King 1997) and cats (Aitkin and Jones 1992) have confirmed that nBIC neurons are acoustically responsive and have spatially tuned receptive fields. The tracing data presented here show that nBIC neurons extend axons that terminate in the dSC, suggesting that this pathway is also likely to provide a major route in by which auditory information reaches the SC in rats.…”
Section: Multisensory Circuits In the Slice: Specificity Of Afferent mentioning
confidence: 98%
“…Previous studies in several species (reviewed in King et al 1998a) have indicated that the dSC receives a substantial auditory projection from the inferior colliculus (IC), the largest component of which comes from the nBIC. An IC-to-dSC projection has also been described in the rat (Cadusseau and Roger 1985;Druga and Syka 1984), but the regions of the IC that supply the SC afferents have not been identified.…”
Section: R E S U L T S Nbic Projection To the Scmentioning
confidence: 99%
See 1 more Smart Citation
“…Further areas of consideration include higher centres implicated in the coding of auditory space, such as the superior colliculus (King et al 1998;King et al 2000;Middlebrooks and Knudsen 1984) and the primary auditory cortex (King et al 2000). In order to promote binaural processing in children with bilateral cochlear implants, an understanding of the effect of deafness on the development of these important auditory centres is necessary.…”
Section: Physiology Of Binaural Hearingmentioning
confidence: 99%
“…As expected from this location, the NBIC receives dense projections from the ipsilateral IC (Kudo and Niimi, 1980). 8) The NBIC innervates densely the ipsilateral and contralateral SC and these projections seem essential for the emergence of a map of auditory space in the intermediate and deep layers of the SC (King et al, 1998b;Nodal et al, 2005). 9) The connections between the NBIC and the SC are reciprocal, as the NBIC receives significant, topographically organized input back from the ipsilateral SC (Doubell et al, 2000).…”
Section: Other Tectotectal Projectionsmentioning
confidence: 66%